Confronting dark academia: A Stoic strategy of acceptance and resistance - Dunne, Neil (My University, 2025)
Neoliberal annexation of universities results in ‘dark academia’, a state associated with stress, anxiety, exhaustion, guilt, fear and burnout. Accounting’s professional commitments and narrow teaching render our discipline especially culpable. Although prior research tends to describe the cause (neoliberalism) and effect (deleterious mental health) of dark academia, I argue for a nuanced and novel characterization of its nature. Specifically, I identify and describe its five ‘values’, namely individualism, illusion, inequality, isomorphism and infinitude. I then argue how Stoic philosophy can be deployed to confront these values. Specifically, in the autoethnographic tradition and mobilizing the Meditations of Marcus Aurelius, I show how academics can accept and yet also resist dark academia’s values. I also challenge prior conceptualization of Stoicism as an impractical and self-centered philosophy by examining how it can realistically and pro-socially benefit the academic community in general. This research may be especially timely for marginalized members of our community, such as junior faculty and PhD students. It illuminates the untapped potential of Stoic philosophy to better understand and confront individual and community crises.
PUBLISHED
Keywords: Accounting academia; neoliberalism; Stoicism; Marcus Aurelius; autoethnography